Nazarbayev University multigrasp hand with bidirectional tendon actuation - Tursynbek, I.; Zhakatayev, A. T.; Varol, H. A. (Nazarbayev University, 2014)
Robotic hands are being used in various areas such as industrial automation, medical robotics, and defense. In this work, we are presenting the Nazarbayev University Multigrasp Robot Hand with an integrated RGB-Depth camera for intelligent object manipulation. The novelty ofthe project is seen in the creation of an end effector system which obtains higher level autonomy from the base manipulator, being able to recognize target objects, generate approach trajectories and apply corresponding grasping patterns to capture the object.
Keywords: robotic hands; medical robotics; multigrasp robot hand; system; 3D printing technology; silicon coating; sensory module